2012
DOI: 10.1016/j.colsurfb.2011.08.019
|View full text |Cite
|
Sign up to set email alerts
|

The influence of physical properties and morphology of crystallised lactose on delivery of salbutamol sulphate from dry powder inhalers

Abstract: The aim of this work was to investigate the mechanistic evaluation of physicochemical properties of new engineered lactose on aerosolisation performance of salbutamol sulphate (SS) delivered from dry powder inhaler (DPI). Different crystallised lactose particles were obtained from binary mixtures of butanol:acetone. The sieved fractions (63-90 μm) of crystallised lactose were characterised in terms of size, shape, flowability, true density and aerosolisation performance (using multiple twin stage impinger (MSL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 57 publications
0
38
0
Order By: Relevance
“…Optical image analysis microscopy was employed to quantify shape of the HPMC E4M and K4M particles using several shape descriptors including roundness [21] and roughness [22].…”
Section: Particle Shape Analysismentioning
confidence: 99%
“…Optical image analysis microscopy was employed to quantify shape of the HPMC E4M and K4M particles using several shape descriptors including roundness [21] and roughness [22].…”
Section: Particle Shape Analysismentioning
confidence: 99%
“…For example, it has been shown that higher amounts of drug could be delivered to lower airway regions by decreasing the mean size of either drug particles 8 or carrier particles. 9,10 The presence of fine particles on the carrier surface has improved the inhalation performance of DPI formulations by decreasing the drug-carrier contact area and consequently reducing drugcarrier adhesion forces. 7,11 Surface morphology of carrier particles has been modified in order to obtain improved drug dispersion properties, where smoother surface 6,12 or higher specific surface area 12,13 produced a higher fine particle fraction of drug.…”
Section: Introductionmentioning
confidence: 99%
“…Liberation of particles from the carrier surfaces is dictated by the magnitude of drug-carrier adhesive forces, and excessive adhesive forces could prevent detachment of drug from the carrier surfaces, leading to poor detachment (18,(31)(32)(33)(34)(35)(36), therefore an increase in the surface roughness of SHL particles could be assumed to result in the reduction in the particle-carrier adhesive forces and subsequently leading to the improved detachment efficiency. In fact, such an assumption was supported by the findings from a previous study (15).…”
Section: In Vitro Aerosol Deposition Studiesmentioning
confidence: 99%